2016
DOI: 10.1111/ijtd.12073
|View full text |Cite
|
Sign up to set email alerts
|

Psychological capital, career identity and graduate employability in Uganda: the mediating role of social capital

Abstract: This paper seeks to evaluate the relationship between psychological capital, career identity, social capital and graduate employability. We also seek to evaluate the mediating role of social capital on the relationships between psychological capital, career identity and graduate employability in Uganda. A population of 480 unemployed young people undertaking a skills development and training program by Compassion International was surveyed providing a sample of 215 respondents. Statistics revealed a significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 57 publications
1
33
0
2
Order By: Relevance
“…Moreover, previous research revealed the association between PsyCap and workers' perceptions of employability, which is defined as the individual perception of his/her possibilities to achieve a new job, and job security [17,22]. For example, Ngoma and Ntale [22] found a positive relationship between PsyCap and employability among unemployed people. Furthermore, Olaniyan and Hystad [17] showed that PsyCap was negatively related to the job insecurity of maritime industry workers.…”
Section: Psycap Perceived Employability and Job Insecuritymentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, previous research revealed the association between PsyCap and workers' perceptions of employability, which is defined as the individual perception of his/her possibilities to achieve a new job, and job security [17,22]. For example, Ngoma and Ntale [22] found a positive relationship between PsyCap and employability among unemployed people. Furthermore, Olaniyan and Hystad [17] showed that PsyCap was negatively related to the job insecurity of maritime industry workers.…”
Section: Psycap Perceived Employability and Job Insecuritymentioning
confidence: 95%
“…The literature has highlighted the relevance of PsyCap with regard to career [16,19] and work attitudes [14,20,21]. Moreover, previous research revealed the association between PsyCap and workers' perceptions of employability, which is defined as the individual perception of his/her possibilities to achieve a new job, and job security [17,22]. For example, Ngoma and Ntale [22] found a positive relationship between PsyCap and employability among unemployed people.…”
Section: Psycap Perceived Employability and Job Insecuritymentioning
confidence: 99%
“…College graduates have always been an important part of high-level human resources. In recent years, the increasingly saturated job market has brought great employment pressure to the graduates (Ngoma & Ntale, 2016). At present, there are many factors affecting the selection of college students' employment areas, including employment policy, employment situation, family background, their own values and personality traits.…”
Section: Introductionmentioning
confidence: 99%
“…Based on a large amount of data, Larson made an in-depth study on the improvement of job burnout by positivity psychological quality, and found that psychological capital such as expectation is negatively correlated with job burnout, and the overall psychological capital of workers can better predict the job burnout mood of teachers than single factors such as self-cognition, perseverance. expectation and self-esteem, and overall psychological capital can well predict the demission risk of employees (Ngoma & Ntale, 2016). Based on Li's measurement table, Jensen obtained the job burnout situation of the teachers in a higher vocational and technical school through the on-the-spot questionnaire survey, and combined with the concept of psychological capital, analyzed how the positivity psychological quality played a role in the vocational identification in a bid to improve teachers' burnout psychology (Oliver, Bibik, Chandler et al, 1988).…”
Section: Introductionmentioning
confidence: 99%